Synthesis and swelling behaviour of hydrophobically modified responsive polymers in dilute aqueous solutions - Iyer, N. P.; Hourdet, Dominique; Badiger, Manohar V.; Chassenieux, Christophe; Perrin, P.; Wadgaonkar, P. (Polymer, 2005)
New series of associating polymers were synthesised in order to investigate opposite behaviours of hydrophobically modified water-soluble polymers and thermoresponsive water-soluble polymers carrying LCST stickers. On the basis of a poly(acrylic acid) backbone, amino-terminated poly(N-isopropylacrylamide), poly(ethylene oxide-co-propylene oxide) and/or dodecyl chains were grafted following a reaction of condensation activated by carbodiimide. Two homologous series of well-defined single grafted and double grafted copolymers were obtained, with double grafted chains containing both C12 and LCST grafts. The dilute solution properties of these copolymers were carefully studied by capillary viscometry. At low salt concentration and below the LCST of the grafts, the swelling properties of macromolecular chains are controlled either by intramolecular associations between hydrophobes, excluded volume effect exerted by hydrophilic grafts or by a balance between these opposite interactions. The deswelling of macromolecular chains, induced by hydrophobic interactions, is amplified at higher ionic strength and more particularly above the transition temperature of the side chains. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: associating polymers; poly(acrylic acid); viscometry

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Swelling and mechanical behavior of modified poly(vinyl alcohol)/laponite nanocomposite membranes - Nair, Shubhangi H.; Pawar, Kiran C.; Jog, Jyoti Prakash; Badiger, Manohar V. (Journal of Applied Polymer Science, 2007)
Nanocomposite (NC) membranes based on hydrophobically modified PVA and laponite were synthesized with varying laponite content in the feed. The incorporation of laponite in NC membranes was investigated by FTIR spectroscopy and thermogravimetric analysis. The swelling ratio of membranes was determined as a function of temperature and laponite content. Swelling studies of NC membranes exhibited the decrease in swelling with an increase in laponite content in the NC membranes. The swelling ratio of NC membrane with 20% laponite slightly increased with an increase in temperature. Dynamic mechanical analysis showed the systematic increase in storage modulus with laponite content, which indicates the enhancement of mechanical property upon laponite addition. There was also a decrease in the tan 6 peak values of NC membranes with an increase in laponite content in NCs. The permeabilities through NC membranes as a function of solute size and laponite content were studied and the results showed molecular screening based on size. The permeability of solute reduced due to the presence of well-dispersed laponite in the NC. (c) 2006 Wiley Periodicals, Inc.
Keywords: Dynamic mechanical analysis; laponite; membranes; nanocomposite hydrogel; poly(vinyl alcohol)

Synthesis and self-assembling properties of alpha,omega-hydroxy-poly(ethylene oxide) end-capped with 1-isocyanato-3-pentadecylcyclohexane - Kadam, Vijay S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Hourdet, Dominique (Polymer, 2008)
A novel hydrophobic compound, 1-isocyanato-3-pentadecylcyclohexane (PDC) issued from a renewable resource material (Cashew Nut Shell Liquid), is used to end-cap poly(ethylene oxide) (PEO) of different molecular weights. The synthesis, characterization and self-assembling properties of these new associating polymers are reported. In aqueous solution, PDC modified PEOs self-associate into micellar structures which are characterized by neutron scattering. Using a star-polymer model with sticky hard sphere interactions, it is shown that the characteristics of the micelles mainly depend on the size of the PEO chain. In the case of PDC stickers, the aggregation number decreases from 25 to 17 with increasing molecular weight of PEO, from 10 to 20 kg/mol, respectively. The temperature directly impacts the interaction potential between the hydrophilic coronas of PEO which become less repulsive with increasing temperature. Rheological measurements, performed in dilute solution, clearly demonstrate that PEO micelles self-associate into open supramolecular structures. The correlation length of these loose clusters increases with polymer concentration and the hierarchical self-assembly follows the rules of the percolation theory. The sol/gel transition takes place at the overlap concentration of clusters. In semi-dilute solution, the viscoelastic properties of PDC end-capped PEOs are well described by the Maxwell model with a single relaxation mode. The characteristic time of the network follows an Arrhenius temperature dependence with an activation energy of 70 kJ/mol, in very good agreement with the size of PDC stickers. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Hydrophobically end-capped; poly(ethylene oxide); Star micelles

Synthesis and characterization of thermo-sensitive graft copolymer of carboxymethyl guar and poly(N-isopropylacrylamide) - Gupta, Nivika R.; Ghute, Pallavi P.; Badiger, Manohar V. (Carbohydrate Polymers, 2011)
Thermo-responsive graft copolymers of carboxymethyl guar [CMG] and semitelechelic poly(N-isopropylacrylamide) [PNIPAm] were synthesized by coupling reaction between them using a water-soluble coupling agent namely, 1-(3-(dimethylamino) propyl)-3-ethyl carbodiimide hydrochloride [EDC]. The incorporation of PNIPAm into CMG was confirmed by FT-IR and NMR spectroscopy. The graft copolymers, CMG-g-PNIPAm showed enhanced viscosity as compared to the unmodified CMG in the semi-dilute regime. Due to the presence of a LCST side chains [PNIPAm], the graft copolymers exhibited thermo-responsive nature with respect to temperature which was investigated using pyrene fluorescence probe studies. Although the thermo-responsive property was observed, the thermo-thickening behavior was not seen in these polymers. The graft copolymers in the semi-dilute regime (C(p) approximate to 10-20 g/L) showed viscoelastic properties and the relaxation time, tau, could be obtained from the crossover of frequency (oh) of storage modulus (G') and loss modulus (G `') in the oscillatory experiments. The activation energy `E(a)' of associations was investigated using the time temperature superpsition (TTS). These thermo-responsive polymers along with the biodegradability of CMG can have potential application as industrial thickening agent. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Poly(N-isopropylacrylamide); Thermo-sensitivity and graft copolymer

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

Self-assemblies of nucleolipid supramolecular synthons show unique self-sorting and cooperative assembling process - Nuthanakanti, Ashok; Walunj, Manisha B.; Torris, Arun; Badiger, Manohar V.; Srivatsan, Seergazhi G. (Nanoscale, 2019)
The inherent control of the self-sorting and co-assembling process that has evolved in multi-component biological systems is not easy to emulate in vitro using synthetic supramolecular synthons. Here, using the basic component of nucleic acids and lipids, we describe a simple platform to build hierarchical assemblies of two component systems, which show an interesting self-sorting and co-assembling behavior. The assembling systems are made of a combination of amphiphilic purine and pyrimidine ribonucleoside-fatty acid conjugates (nucleolipids), which were prepared by coupling fatty acid acyl chains of different lengths at the 2 `-O- and 3 `-O-positions of the ribose sugar. Individually, the purine and pyrimidine nucleolipids adopt a distinct morphology, which either supports or does not support the gelation process. Interestingly, due to the subtle difference in the order of formation and stability of individual assemblies, different mixtures of supramolecular synthons and complementary ribonucleosides exhibit a cooperative and disruptive self-sorting and co-assembling behavior. A systematic morphological analysis combined with single crystal X-ray crystallography, powder X-ray diffraction (PXRD), NMR, CD, rheological and 3D X-ray microtomography studies provided insights into the mechanism of the self-sorting and co-assembling process. Taken together, this approach has enabled the construction of assemblies with unique higher ordered architectures and gels with remarkably enhanced mechanical strength that cannot be derived from the respective single component systems.

Studies on the use of sodium polyacrylate (SPA) for low-salt animal skin preservation - Balasubramanian, Venkatakrishnan; Velappan, Brindha; Vijayan, Sandhya Kurvilla; Jabamani, Hepzibah; Nagarajan, Vedaraman; Victor, John Sundar; Ranganath, Suresha P.; Badiger, Manohar V.; Chinnaraj, Velappan kandukalpatti; Chellappa, Muralidharan (Environmental Science and Pollution Research, 2019)
Salt-based preservation is practiced for decades in the leather industry because of its versatility, cost-effectiveness, and availability. The salt removed from the soaking process causes significant pollution including organic and elevated total dissolved solids (TDS). Hence, a low-salt skin preservation method using commercial sodium polyacrylate with a reduced quantity of sodium chloride aiming to retain leather properties and pollution reduction was the principal focus of the study. Commercial sodium polyacrylate initially characterized for water absorption capacity along with structural and functional properties is confirmed by NMR and IR spectroscopic techniques. In preliminary experiments, the process parameters attained optimized conditions of sodium polyacrylate (SPA) quantity (5%), a minimal amount of salt (15%), and contact time (4 h) required for skin preservation. Besides, reusability studies after SPA recovery (95%) were applied to skins with an optimized quantity of SPA and salt subsequently stored for 15 days along with control (40% salt). The results revealed that SPA with low salt aided an adequate curing efficiency with a substantial reduction (> 65%) of TDS and comparable physical and organoleptic properties on par with the conventional method. Overall, SPA supported low-salt skin preservation reduces pollutant load (TDS) caused due to using of 40% sodium chloride in the conventional curing process.

Sulfonated polyvinyl alcohol ionomer membrane favoring smooth electrodeposition of zinc for aqueous rechargeable zinc metal batteries - Vijayakumar, Vidyanand; Torris, Arun; Kurian, Maria; Mathew, Megha Mary; Ghosh, Meena; Khairnar, Ajay B.; Badiger, Manohar V.; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2021)
One of the failure mechanisms of aqueous rechargeable zinc metal batteries (AZMBs) involves high surface area zinc (HSAZ)/dendrite-like deposits over the Zn-metal anode during long-term cycling. Negatively charged (anionic) polymeric ionomer electrolyte membranes and separators are known for suppressing the dendrite-/HSAZ-induced failure of AZMBs. However, the preparation of cost-effective and non-fluorinated ionomers from cheap and environmentally friendly polymers is essential to leverage the feasibility of AZMBs. The current work demonstrates the potential of an ionomer electrolyte membrane (P-AS-C-Zn) made by the crystallization-induced physical cross-linking of sulfonated poly (vinyl alcohol) (PVS) and poly (vinyl alcohol) (PVA) as a dendrite-/HSAZ-inhibiting separator for AZMBs. The P-AS-C-Zn membranes exhibited excellent Zn plating/stripping behavior with a stable voltage vs. time profile beyond 1100 h, compared to their neutral PVA-C-Zn counterpart without any ionomer character (cell failure at close to 280 h). Applying the optimized P-AS-C-Zn membrane in a MnO2||Zn full cell helps retain about 50% of the initial capacity close to 600 cycles in the absence of extra manganese salt in the electrolyte, which is indeed promising.